2015
DOI: 10.1123/jpah.2014-0233
|View full text |Cite
|
Sign up to set email alerts
|

Sitting Time and Quality of Life in Older Adults: A Population-Based Study

Abstract: In this study, older adults who sat the most presented the worst scores in the physical domain and social participation facet of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 6 publications
3
34
2
4
Order By: Relevance
“…Presumably, behavioral aspects during screen time (such as eating and drinking) could be the factors that cause TV‐viewing sitting more harmful to health than other types of sitting. Negative associations between sedentary behavior and HRQoL have been previously reported in older adults, although there is also recent evidence of a positive association of domain‐specific sedentary time (reading time) with mental‐based HRQoL in middle‐aged adults . Nevertheless, in our study, the Lowest tertile averaged the most daily time sitting.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Presumably, behavioral aspects during screen time (such as eating and drinking) could be the factors that cause TV‐viewing sitting more harmful to health than other types of sitting. Negative associations between sedentary behavior and HRQoL have been previously reported in older adults, although there is also recent evidence of a positive association of domain‐specific sedentary time (reading time) with mental‐based HRQoL in middle‐aged adults . Nevertheless, in our study, the Lowest tertile averaged the most daily time sitting.…”
Section: Discussioncontrasting
confidence: 65%
“…Presumably, behavioral aspects during screen time (such as eating and drinking) could be the factors that cause TV-viewing sitting more harmful to health than other types of sitting. Negative associations between sedentary behavior and HRQoL have been previously reported in older adults, 30,31 Nevertheless, in our study, the Lowest tertile averaged the most daily time sitting. This indicates that due to the lack of PA, this relationship could be the most harmful to health compared to all the other tertiles.…”
Section: Discussioncontrasting
confidence: 61%
“…The present study findings support the results of previous studies that prolonged sedentary time is significantly associated with quality of life in adults with visual impairments or general adults or in middle-aged and older adults with osteoarthritis [3,5,14]. In contrast with previous studies indicating that men have lower quality of life than women, the present study show that the quality of life was lower in women than men when sitting for 7.5 or more h/d in older adults or among older men [9,10]. These results suggest that a comparative study is needed by selecting different subjects.…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, sedentary time could be an important factor for successful aging and quality of life in middle-aged and older adults. Unfortunately, aside from the negative influences on the successful aging [7], the relationship between sedentary time and quality of life in middle-aged and older adults remains minimally explored [9,10]. In this context, the association of sedentary time with quality of life in middle-aged and older adults should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that low daily physical activity (DPA) is associated with poor QoL in older adults [9, 10]. Furthermore, previous studies of frail persons have demonstrated that muscle strength, as represented by handgrip strength [3], plays an important role regarding QoL [6, 7, 11].…”
Section: Introductionmentioning
confidence: 99%